The Role of Mindfulness-Based Interventions in Promoting Mental Health and Emotional Wellbeing for Children and Adolescents - Wong, Cheng Hui (Trinity College (Dublin, Ireland). School of Education, 2022)
This paper critically evaluates existing research on the role of mindfulness interventions as a mental health and wellbeing tool for children and adolescents. It also investigates its potential benefits as well as associated challenges when implemented in Educational Setting by means of a literature review underpinned by the systematic literature review approach. Findings revealed mixed results of the effectiveness of mindfulness interventions to promote mental health and emotional wellbeing in students. However, benefits such as academic achievement and improved student teacher relationships were reported. Challenges such as negative attitudes from school staff and disinterest from students were indicated as the biggest challenge to implement mindfulness in schools. Thereby, mindfulness based interventions are proposed as a potentially beneficial intervention tool for children and adolescents if considerations for existing limitations are adapted to optimise its efficacy. Recommendations for further research and future implications for educational policy makers were also discussed at the end.
Keywords: Master in Education Special Educational Needs; Education